2014
DOI: 10.1159/000360537
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic Fluid Embolism Induces Uterine Anaphylaxis and Atony following Cervical Laceration

Abstract: Amniotic fluid embolism (AFE) is a rare, high-risk obstetric complication primarily found in the lungs and potentially related to anaphylaxis. Tryptase release from the mast cell reflects anaphylaxis. Case report and findings: A female, aged over 40 years, presented with uterine atony and lethal hemorrhage after induced vaginal labor. Cervical laceration was accompanied by severe hemorrhage. Stromal edema and myometrial swelling were consistent with uterine atony. Alcian blue staining and zinc coproporphyrin i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 7 publications
(9 reference statements)
2
8
0
Order By: Relevance
“…Immunohistochemical techniques also revealed an increased count of CD88‐positive cells within the uterine stroma, prominent tryptase halos around activated mast cells, elastase‐positive neutrophils, and CD68‐positive macrophages in the myometrium of DIC type PPH (Fig. a‐d) . Increased CD88 immunostaining of inflammatory cells was found to be related to the edematous stroma and swollen myometrium, suggesting an association between complement activation and inflammation as well as uterine atony .…”
Section: Pathological Examination Of Lung and Uterus In Afementioning
confidence: 86%
See 2 more Smart Citations
“…Immunohistochemical techniques also revealed an increased count of CD88‐positive cells within the uterine stroma, prominent tryptase halos around activated mast cells, elastase‐positive neutrophils, and CD68‐positive macrophages in the myometrium of DIC type PPH (Fig. a‐d) . Increased CD88 immunostaining of inflammatory cells was found to be related to the edematous stroma and swollen myometrium, suggesting an association between complement activation and inflammation as well as uterine atony .…”
Section: Pathological Examination Of Lung and Uterus In Afementioning
confidence: 86%
“…a‐d) . Increased CD88 immunostaining of inflammatory cells was found to be related to the edematous stroma and swollen myometrium, suggesting an association between complement activation and inflammation as well as uterine atony . We proposed these features of “Postpartum acute myometritis (PAM)” as a histological character in PPH of unknown etiology secondary to uterine atony, widely regarded as uterine‐type AFE (Fig.…”
Section: Pathological Examination Of Lung and Uterus In Afementioning
confidence: 99%
See 1 more Smart Citation
“…As a result, Clark et al [16] proposed the term 'Anaphylactoid Syndrome of Pregnancy' -an entity that has some commonality with the systemic inflammatory response syndrome. The most often suspected sites of amniotic fluid entry are the endocervix and the lower uterine segment, with endocervical veins, uterine trauma sites, and the placental attachments likely involved in the egress of fetal tissue [17].…”
Section: Pathogenesis and Pathophysiologymentioning
confidence: 99%
“…Anaphylaxis is the most frequently recorded symptoms and also associated with complement activation. More recently, Tamura et al 40 reported that AFE can induce uterine atony, DIC, and lethal hemorrhage possibly through anaphylaxis and complement activation. The clinical symptoms differ according to the subtypes of AFE.…”
Section: Complement Activationmentioning
confidence: 99%